Modification of cotton gauze using Cynodon dactylon (Bermuda grass) and assessment of the chemical and antimicrobial properties - Umme Lewara Bristi; Abdur Rahman; Sadit Bihongo Malitha; Oishee Rahman; Sharmin Shoukat (Scientific Reports)
Abstract Bermuda grass (Cynodon dactylon) is a tropical grass found in all tropical and subtropical areas. It is widely found in Bangladesh and well known for its antimicrobial properties. Cotton gauze is a woven cloth which is used for wound dressing and wound cushioning. Incorporating antimicrobial properties to cotton gauze may promote wound healing, prevent infection and lower healthcare costs. The objective of this study is to create cotton bandages treated with herbal extracts containing antimicrobial properties. These eco-friendly bandages aim to facilitate wound healing without the need for additional dressing components. To achieve this goal, Bermuda grass (Cynodon dactylon) was extracted and pre-mordanting, meta-mordanting and post-mordanting methods were followed in this study. Several tests were conducted, including Fourier Transform Infrared Spectroscopy (FTIR), anti-bacterial test, skin irritation test, gram-positive and gram-negative bacterial tests, color fastness to wash test, Scanning Electron Microscopy (SEM), and Energy-dispersive X-ray (EDX). The herbal treatment performed well in all these tests. The FTIR indicated the presence of phytochemicals in the treated samples. The cloth demonstrated excellent retention of the Cynodon dactylon treatment extract even after washing, achieving a grade of 4–4.5 on the grayscale. Additionally, it exhibited a remarkable antibacterial rate when tested against Staphylococcus aureus, although there was less reduction when tested against E. coli. The skin irritation test revealed negligible acute dermal irritation in the sampled fabric. These treated samples provide a promising prospect for the development of medical bandages, given the growing need in the medical industry for environmentally friendly goods.